All Digital Light Processing‐3D Printing of Flexible Sensor. Issue 2 (11th November 2022) - Xiao, Ting; Chen, Yang; Li, Qi; Gao, Yang; Pan, Likun; Xuan, Fuzhen
Abstract: Flexible sensor with high sensitivity, high durability, and facile fabrication process has promising applications in structural health monitoring, human–machine interface, and soft robotics areas. Digital light processing‐3D (DLP‐3D) printing can print flexible sensor in a scalable process. However, to achieve all DLP‐3D printing of flexible sensor, there still exist challenges of how to print sensing units with high sensitivity to external stimuli, interconnectors with high conductive stability at deformations, and robust interfaces between them for long‐term usage. To address this, a hybrid DLP‐3D printing method is developed, including the key steps of printing carbon nanotube/elastomer (MWCNT/EA) as sensing units and selective electrostatic self‐assembly of silver nanowires (Ag NWs) as interconnectors. As a demonstration, a flexible pressure sensor array integrated with amplifier circuit is fabricated by the method. The MWCNT/EA sensing unit with woodpile structure has nine times improved sensitivity than the solid one. The Ag NW interconnector with serpentine configuration shows insensitivity to strain and good mechanical stability. The interface between sensing unit and interconnector is mechanical robust due to the chemical bond formation under ultraviolet radiation. The flexible sensor could detect external stimuli with enhanced signals enabled by integrated amplifier circuit, exhibiting potentials of the method for flexible electronic fabrication. Abstract : A pressure sensor array integrated with an amplifier circuit is fabricated by a hybrid digital light processing‐3D printing technique. The flexible sensor can detect external stimuli with enhanced signals enabled by the integrated amplifier circuit, exhibiting the potentials of the method for flexible electronic fabrication.